Possible fine-tuning of methane activation toward C2 oxygenates by 3d-transition metal-ions doped nano-ceria-zirconia - Kanungo, Subhashree S.; Mishra, Abhaya Kumar; Mhamane, Nitin B.; Marelli, Udaya Kiran; Kumar, Dharmesh; Gopinath, Chinnakonda S. (Inorganic Chemistry, 2022)
In this work, we demonstrate a simple sol-gel technique to prepare metal-ion(s)-doped ceria-zirconia solid solution for efficient catalytic methane activation. The cation -depicting formula units are Ce0.80Zr0.20 (CZ), Ce0.79Zr0.20M0.01 (CZM), and Ce0.79Zr0.20M0.005M10.005 (CZMM1) (M and M1 = V, Mn, Fe, Co, and Cu), employed for undoped, mono-metal-ion -doped, and bi-metal-ion-doped solid solutions, respectively. Methane activation with Mn, Fe, Cu mono-metal-ion-doped CZ favors the C1 product, while CZCo assists C-C coupling with the formation of acetaldehyde. On the other hand, the Co-and Fe -doped bi-metal-ion combination catalyst (CZCoFe) shows significant ethanol but predominant formic acid formation. This is further promoted by the Co + V bi-metal-ion combination (CZCoV) catalyst, and it shows ethanol as the major product along with methyl hydrogen peroxide, methanol, and formic acid as minor products. An impressive ethanol yield of 93 mu mol/g h with 76% selectivity obtained with the CZCoV catalyst is at par with that obtained with noble-metal-based catalysts under comparable reaction conditions. When Co and V content was increased two and four times from 0.005 to 0.01 and 0.02, ethanol yield increased at the expense of formic acid. The 213 mu mol/g h ethanol yield (86% selectivity) observed with Ce0.76Zr0.20Co0.02V0.02 is probably the highest observed. The partial oxidation of CH4 in Co-based bi-metal combinations (Co + V or Co + Fe) suggests the synergistic effect of doped metal ions owing to the heterogeneous near -neighbor environment. The present results are attributed to the surface heterogeneity between the host and the dopants, which selectively promotes methane activation as well as C-C coupling. This indicates a large scope to tune the activity of partial oxidation of methane and product selectivity with different metal-ion(s) combinations.

Peptide functionalization with dithioate and trithioate groups: A CS2-mediated solid-phase approach - Shinde, Dinesh R.; Bodake, Supriya Mahadev; Marelli, Udaya Kiran (Organic Letters, 2025)
The dithiocarbamate group is an important class of compounds whose presence in small molecules and peptides leads to antimicrobial, anticancer, and enzyme inhibition properties. This study introduces an efficient and selective method for incorporating dithioate and trithioate moieties into amino acids and peptides using CS2 chemistry under mild conditions. Utilizing a N,N-diisopropylethylamine (DIPEA)-CS2-benzyl chloride system, we achieved modifications at the N-terminal amines and the side chains of Lys and Cys residues through solid-phase peptide synthesis (spps). The method exhibits excellent yields and broad compatibility with diverse amino acids, their protection groups, peptide chemistry reagents, and varied peptide sequences. Notably, the successful incorporation of trithioate groups into peptides via cysteines, reported here for the first time, expands the functional repertoire of peptide chemistry, offering new possibilities for peptide-based drug design and related applications.

Peptide-triazolobenzodiazepine hybrids: a catalyst-free on-resin strategy to build complex therapeutic motifs into peptides - Kamble, Sandip Sushila Mohan; Bodake, Supriya Mahadev; Marelli, Udaya Kiran (Chemistry-A European Journal, 2025)
The merger of peptide and heterocyclic chemistry presents significant opportunities for enhancing the structural and functional diversity of therapeutic agents. In this study, we introduce a streamlined on-resin method to modify peptides at the N-terminus amines and the side chain amines of Lys/Orn amino acids by incorporating the biologically active triazolobenzodiazepine scaffold. In the presented solid-phase peptide synthesis (SPPS), the triazolobenzodiazepine core is formed on-resin through a combination of N-alkylation, amide bond formation, and an alkyne-azide 1,3-dipolar cycloaddition, of which the latter two happen as a single-step one-pot reaction- proceeding under mild conditions without metal catalysts. This protocol tolerates a wide variety of amino acids and functional groups, providing a versatile method for synthesizing peptide-triazolobenzodiazepine hybrids. Using orthogonal protection group strategies, we further demonstrate the method's adaptability for two site modifications in peptides involving both the N-terminus and Lys side chain amines. These modifications enhance the scope of ``peptide medicinal chemistry'' by creating multifunctional peptides with potential therapeutic applications. The method's compatibility with SPPS, room temperature conditions, and elimination of metal catalysis make it an efficient and powerful tool for peptide modification.
Keywords: hybrid peptides; peptide chemistry; peptide modification; spps compatibility; triazolobenzodiazepines